ASESMENT PENDIDIKAN KARAKTER DAN MORAL ANAK USIA DINI DENGAN BASIS KEARIFAN LOKAL - Didik Iswahyudi; Mochammad Ramli Akbar (Jurnal Moral Kemasyarakatan, 2017)
This study aims to assess and describe the process of character education and moral of early childhood with the basis of local wisdom to know the advantages and disadvantages of strategies and processes that have been applied. This research uses the qualitative case study method, & using Miles & Hubberman model analysis technique. This research was conducted in Bandungrejosari Village, Malang City. Based on the research conducted on the advantages of learning process of character and morale of early child have superiority in theme and design which is not in conflict with vision, mission, and goals either from institution or from regulation and appeal from stakeholder, compiled together by all parties with local wisdom identification capital sourced from existing local content and implemented in a varied and comprehensive manner through careful planning and monitoring of joint evaluations. While the weakness of the design is the process of character and moral learning that exist in the location of research is the element of subjectivity of teachers who are still high and the limited resources to explore, analyze, and identify local wisdom from local content so that the character and morale are trying to be formed still at the limit of applying local content and have not formed personality based on local wisdom.